2022
DOI: 10.3389/fmolb.2022.1003227
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic memory contributing to the pathogenesis of AKI-to-CKD transition

Abstract: Epigenetic memory, which refers to the ability of cells to retain and transmit epigenetic marks to their daughter cells, maintains unique gene expression patterns. Establishing programmed epigenetic memory at each stage of development is required for cell differentiation. Moreover, accumulating evidence shows that epigenetic memory acquired in response to environmental stimuli may be associated with diverse diseases. In the field of kidney diseases, the “memory” of acute kidney injury (AKI) leads to progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 230 publications
0
5
0
Order By: Relevance
“…Acute kidney injury and CKD are intercorrelated (Okusa et al 2009 ; Coca et al 2012 ). Notably, patients recovering from acute kidney injury may be at risk of CKD due to nephron loss, incomplete repair, inflammation, fibrosis, and epigenetic changes (Wang and Zhang 2022 ; Tanemoto et al 2022 ). As our study lacked serial clinical and laboratory parameters, such as blood pressure or urine protein levels, further prospective studies are needed to examine the causality and time course of the association between intravitreal VEGF inhibitors and risk of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury and CKD are intercorrelated (Okusa et al 2009 ; Coca et al 2012 ). Notably, patients recovering from acute kidney injury may be at risk of CKD due to nephron loss, incomplete repair, inflammation, fibrosis, and epigenetic changes (Wang and Zhang 2022 ; Tanemoto et al 2022 ). As our study lacked serial clinical and laboratory parameters, such as blood pressure or urine protein levels, further prospective studies are needed to examine the causality and time course of the association between intravitreal VEGF inhibitors and risk of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…responsible for the most important functions of synthesis of essential proteins, ion transport, an increase in copies of genes encoding essential proteins, and others. New structures are formed, which increases the functional capacity of the system and brings the organism to a new level of functioning required for the duration of the environmental factor (Chu et al, 2022;Tanemoto et al, 2022). The number of newly created structures is called the "structural cost of adaptation".…”
Section: The Social and Demographic Situationmentioning
confidence: 99%
“…This pathogenetic mechanism is called local wear and tear of the systems dominant in adaptation. All of these mechanisms are characteristic of long-term exposure to radiation (Chu et al, 2022;Tanemoto et al, 2022).…”
Section: The Social and Demographic Situationmentioning
confidence: 99%
“…Kroening et al [ 33 ] showed that hypoxia reduces the expression of CTGF (connective tissue growth factor, a stimulator of extra cellular matrix) in human kidney epithelial cells with the involvement of DNA methylation [ 33 ]. Some publications describe a so-called hypoxic memory that drives the transition of acute kidney injury (AKI) to CKDs [ 34 , 35 ]. Epidemiological studies showed that even after AKI, a certain percentage of patients who recovered from AKI develop CKD [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some publications describe a so-called hypoxic memory that drives the transition of acute kidney injury (AKI) to CKDs [ 34 , 35 ]. Epidemiological studies showed that even after AKI, a certain percentage of patients who recovered from AKI develop CKD [ 34 , 35 ]. Therefore, renal hypoxia can also induce the establishment of cellular memory.…”
Section: Introductionmentioning
confidence: 99%